Odpowiedź :
Odpowiedź:
zad.11
a) 3-7= - 4
3-26= - 23
b) -1-4= - 5
-1-6= - 7
c) 3 i 1/2- 2 = 1 i 1/2
- 2 i 1/2 -5= - 7 i 1/2
zad.12
a) 8-2 = 8+(-2)
bo: 8-2= 6 i 8+(-2)= 8-2= 6
b) -4-3 = (-4)+(-3)
-4-3= - 7 i (-4)+(-3)= -4-3= - 7
c) 6-11 ≠ -6 +11
bo: 6-11= -5 ; -6 +11 =5
d) -2-3 = (-2) + (-3)
bo: -2-3= - 5 i (-2)+(-3)= -2-3= - 5
Szczegółowe wyjaśnienie:
Odpowiedź:
zad. 11
a) 3 - 7 = -4
3 - 26 = -23
b) -1 - 4 = -5
-1 - 6 = -7
c) 3 1/2 - 2 = 1 1/2
-2 1/2 - 5 = -7 1/2
zad. 12
a) 8 - 2 = 8 + (-2)
b) -4 - 3 = (-4) + (-3)
podpunkty c i d w załączniku
Mam nadzieję że dasz mi naj